Diasporic homecomings to Kurdistan Region of Iraq: Pre- and post return experiences shaping motivations to re-return - Bahar Baser; Mari Toivanen (Sage Publications Ltd., 2025)
This article examines the dynamics of voluntary return migration to the Kurdistan region of Iraq (KRI) in the post-Saddam period and provides a contextualized analysis of the returnees’ experiences in a rapidly shifting geopolitical situation in Kurdistan. It specifically focuses on examining how diasporans’ motivations to return, as well as their plans to re-return, are shaped in relation to their experiences in host societies and in the ‘homeland’. Drawing from qualitative interviews, it shows that Kurdish diasporans’ return can be characterized as ‘diasporic homecoming’ as it is motivated by the desire to contribute to the economic and political development of the KRI. However, the mismatch between expectations and ‘homeland’ realities combined with positive experiences and social capital accumulated in the host country makes plans for re-return more foreseeable and less risky.